Dose-dependent roles for canonical Wnt signalling in de novo crypt formation and cell cycle properties of the colonic epithelium - Hirata, Akihiro; Utikal, Jochen; Yamashita, Satoshi; Aoki, Hitomi; Watanabe, Akira; Yamamoto, Takuya; Okano, Hideyuki; Bardeesy, Nabeel; Kunisada, Takahiro; Ushijima, Toshikazu; Hara, Akira; Jaenisch, Rudolf; et al. (Development, 2013)
There is a gradient of β-catenin expression along the colonic crypt axis with the highest levels at the crypt bottom. In addition, colorectal cancers show a heterogeneous subcellular pattern of β-catenin accumulation. However, it remains unclear whether different levels of Wnt signalling exert distinct roles in the colonic epithelium. Here, we investigated the dose-dependent effect of canonical Wnt activation on colonic epithelial differentiation by controlling the expression levels of stabilised β-catenin using a doxycycline-inducible transgenic system in mice. We show that elevated levels of Wnt signalling induce the amplification of Lgr5+ cells, which is accompanied by crypt fission and a reduction in cell proliferation among progenitor cells. By contrast, lower levels of β-catenin induction enhance cell proliferation rates of epithelial progenitors without affecting crypt fission rates. Notably, slow-cycling cells produced by β-catenin activation exhibit activation of Notch signalling. Consistent with the interpretation that the combination of Notch and Wnt signalling maintains crypt cells in a low proliferative state, the treatment of β-catenin-expressing mice with a Notch inhibitor turned such slow-cycling cells into actively proliferating cells. Our results indicate that the activation of the canonical Wnt signalling pathway is sufficient for de novo crypt formation, and suggest that different levels of canonical Wnt activations, in cooperation with Notch signalling, establish a hierarchy of slower-cycling stem cells and faster-cycling progenitor cells characteristic for the colonic epithelium.
Gesehen am 22.12.2021